The relationship of platelet distribution width with all-cause and cardiovascular mortality in peritoneal dialysis patients - Chunyu Lu; Shuiqin Cheng; Wenjing Fan; Zhihong Zhang; Jinquan Wang (Renal Failure)
Background Cardiovascular disease (CVD) is a major complication in peritoneal dialysis (PD) patients. Previous studies have demonstrated that platelet distribution width (PDW) is associated with cardiovascular events in hemodialysis (HD) patients. In this study, we hypothesized that elevated PDW can predict all-cause and cardiovascular mortality in PD patients.Methods We recruited PD patients for a single-center retrospective cohort study from 1 January 2007, to 30 June 2020. Receiver-operating characteristic (ROC) curves were made to determine the PDW cutoff value for predicting all-cause mortality. The propensity score matching (PSM) method was used to improve the equilibrium between groups. The relation of PDW with all-cause and cardiovascular mortality was analyzed by Cox proportional hazards models. Restricted cubic spline (RCS) models were used to determine whether there was a linear relationship between PDW and all-cause and cardiovascular mortality.Results A total of 720 PD patients were screened, and 426 PD patients were enrolled after PSM. After adjusting for confounders, Cox proportional hazards models showed that the PDW value was positively correlated with the risk of all-cause and cardiovascular mortality (HR = 1.162, 95% CI 1.057–1.278, p = 0.002 and HR = 1.200, 95% CI 1.041–1.382, p = 0.012). The adjusted RCS analysis further showed that the relationship of PDW with all-cause and cardiovascular mortality was linear (p for nonlinearly = 0.143 and 0.062).Conclusion Elevated PDW is independently associated with all-cause and cardiovascular mortality in PD patients.